Let's analyze the steps you provided for solving the equation:
- Starting equation: \(3x - 9x + 1 = 2(-3x + 1) - 1\).
- Simplifying the left side: \(3x - 9x + 1 = -6x + 1\).
- Simplifying the right side: \(2(-3x + 1) - 1 = -6x + 2 - 1 = -6x + 1\).
- Now, we have: \(-6x + 1 = -6x + 1\).
Since both sides of the equation are identical (-6x + 1 = -6x + 1), this means that the equation holds true for all values of \(x\).
Thus, the correct statement is: There are infinitely many solutions to the equation.